(untitled) (Lex localis - Journal of Local Self-Government, 2018)
China’s rapid urbanisation in the past 30 years has been a prominent issue in the world. However, few studies elaborate on the rapid spatial urbanisation from the perspective of local decision makers (in particular the Secretaries of Municipal Party Committees-the SMPCs). Local governors are always seeking promotions as they are in a competitive bureaucratic hierarchy. This research is, therefore, intended to explain the local decision-making driving force of spatial urbanisation by analysing the interaction between local decision makers’ tenures and urban expansion. Based on the panel data of all 286 prefecture-level cities nationwide from 2000 to 2014, Stata 14.0 was applied to implement regression analysis. Research findings show that SMPCs have, in general, great incentives for promoting rapid urban development. Additionally, SMPCs who are transferred from other municipalities implement more rapid and larger-scale urban development than those who are locally promoted.